Otimização da adubação fosfatada para a cultura da melancia irrigada em ambiente semiárido - Pereira, Natanael Santiago (2016)
The watermelon crop has great economic and social importance in the State of Rio Grande do Norte and, in this way, there is a great demand for information for an adequate management of fertilization, particularly for P, due to its dynamics in the soil and its Low availability in many soils of the region. Thus, the objective of this work was to evaluate the production and accumulation of nutrients by the cv. Magnum under the influence of the management of phosphate fertilization. The experiments were carried out in a Cambisol of medium texture, originating from limestone (Upanema-RN) and in a Ultisol of sandy texture (Mossoró-RN), in a randomized complete block design, with four replications. In the limestone experiment, treatments consisted of 76, 168, 275 and 397 kg ha-1 of P2O5, which were applied in two ways: F0- in pre-planting and F1-in pre-planting + cover (50 kg ha-1 of P2O5 by fertigation). Two additional treatments were applied: without phosphate; and with phosphate only in the cover (50 kg ha-1 of P2O5 by fertigation). In the experiment carried out in a sandy soil the treatments consisted of 34, 80, 168 and 206 kg ha-1 of P2O5, which were applied in two ways: F0- in pre-planting and F1-in pre-planting + cover (34 kg ha-1 of P2O5 by fertigation). Two additional treatments were applied: without phosphate; and with phosphate only in the cover (103 kg ha-1 of P2O5 by fertigation). In calcareous soil there was an isolated effect of doses and forms of application on the production characteristics, especially the highest dose of F1 fertilization in relation to F0. However, in general, the additional treatment with 103 kg ha- 1 of P2O5 in fertigation was shown to be more efficient, with commercial productivity equivalent to a dose of 204 kg ha-1 of P2O5 in F1 fertilization. Fertilization F1 provided higher accumulations of P and S, but in general the effects of fertilization were dose-dependent, with treatments F0275 and F1168 in terms of accumulation of biomass and other macronutrients. In sandy soil, there was an isolated effect of doses and forms of application on the production characteristics, especially the highest dose of F1 fertilization in relation to F0. However, in general, the additional treatment with 103 kg ha-1 of P2O5 in fertigation was shown to be more efficient, with commercial productivity equivalent to a dose of 204 kg ha-1 of P2O5 in F1 fertilization. At the dose of 137 kg ha-1 of P2O5, occurred higher accumulations of P in F1 fertilization, both in shoot and fruit. For Ca and Mg, greater accumulations occurred with F1 fertilization only in the vegetative part. Overall, about 50% of total macronutrient demand occurs in the last quarter of the cycle